The Influence Of Social Media, Self-Esteem, Lifestyle, On Consumer Behavior In Purchasing Women's Skincare Products In Gowa District Through Fear Of Missing Out As A Mediation Variable - Fitrah Fahrisah; Syamsu Rijal; Wulan Purnamasari; Nurwahida; Andi Caezar To Tadampali (Citakonsultindo, 2026)
This study aims to analyze the influence of Social Media, Self-Esteem, and Lifestyle on Consumer Behavior in purchasing skincare products among women in Gowa Regency with Fear of Missing Out as a mediating variable. This study used a quantitative approach with a survey method. Data were collected through questionnaires distributed to female skincare users and analyzed using Structural Equation Modeling (SEM). The results of the study indicate that social media, self-esteem, and lifestyle have a positive and significant influence on consumer behavior. These three variables also have a positive and significant influence on fear of missing out. Fear of missing out has been shown to have a positive and significant influence on consumer behavior and acts as a partial mediator in the relationship between social media, self-esteem, and lifestyle on consumer behavior. These findings suggest that consumer purchasing decisions in the digital age are influenced not only by functional needs but also by psychological vulnerabilities and social pressures that arise through digital interactions. This research provides theoretical contributions to the development of consumer behavior studies in the digital age and offers practical implications for developing more ethical marketing strategies in the skincare industry.